2013
DOI: 10.1017/s095026881300109x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of shedding of Verocytotoxin-producingEscherichia coliin children and risk of transmission in childcare facilities in England

Abstract: Exclusion of children with presumptive Verocytotoxin-producing Escherichia coli (VTEC) from childcare facilities until negative stool specimens are obtained is routine practice that disrupts families. We estimated the shedding and exclusion duration and transmission risk in such facilities. The study population comprised 225 children aged <6 years attending 201 childcare facilities in England with microbiologically confirmed VTEC in 2010-2011. We estimated the interval from onset to first negative specimen, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
5
15
0
1
Order By: Relevance
“…Symptoms were self-reported and only available for four of the five health authorities in the province. Despite this, the proportion of cases with symptoms was similar to that observed in other studies (22,42). There is no reason to believe symptoms and outcomes for the same disease would be different for the one health authority from which these data were unavailable.…”
Section: Discussionsupporting
confidence: 82%
“…Symptoms were self-reported and only available for four of the five health authorities in the province. Despite this, the proportion of cases with symptoms was similar to that observed in other studies (22,42). There is no reason to believe symptoms and outcomes for the same disease would be different for the one health authority from which these data were unavailable.…”
Section: Discussionsupporting
confidence: 82%
“…Both symptoms of clinical infection and shedding of STEC O117:K1:H7 seem to be of much longer duration than described in any other group of STEC . The O117:K1:H7 clonal group thus seems to be an excellent colonizer of the human intestine, despite the absence of the eae and saa genes that are considered to be important adherence factors .…”
Section: Chapter 4 Verotoxin/shiga Toxin‐producing (Vtec/stec) O117:mentioning
confidence: 89%
“…The duration of shedding was 18–41 days in patients with non‐O157 infection vs 4 to >43 days in patients with O157:H7 infection. A recent English study reported a median duration of shedding of 31 days among 225 children aged <6 years attending 201 childcare facilities in England with microbiologically confirmed STEC in 2010–2011. In another study, one adult carrier who was involved in a German outbreak of STEC O104:H4 shed the outbreak strain for >7 months .…”
Section: Chapter 4 Verotoxin/shiga Toxin‐producing (Vtec/stec) O117:mentioning
confidence: 99%
“…Le sérogroupe le plus signalé était O157 à tous les ans sauf en 2017, où les cas avec O121 étaient les plus fréquents. (22,42). Il n'existe aucune raison de penser que les symptômes et les résultats pour la même maladie seraient différents dans la seule région sociosanitaire pour laquelle ces données n'étaient pas disponibles.…”
Section: Résultatsunclassified